"[T]he laws need to change to reflect current society": Insights from stakeholders involved in development, review or implementation of policies about adolescent consent for HIV testing, care and research in Kenya. Issue 1 (15th January 2023) - Li, Huangqianyu; Shah, Seema K.; Healy, Elise; Agot, Kawango; Neary, Jillian; Wilson, Kate; Badia, Jacinta; Atieno, Winnie O.; Moraa, Hellen; Meischke, Hendrika; Kibugi, James; Inwani, Irene; et al.
Abstract: Introduction: Engaging adolescents in HIV care and research promotes the development of interventions tailored to their unique needs. Guidelines generally require parental permission for adolescents to receive HIV care/testing or participate in research, with exceptions. Nevertheless, parental permission requirements can restrict adolescent involvement in care and research. To better appreciate prospects for policy reform, we sought to understand the perspectives of stakeholders involved in the development, review and implementation of policies related to adolescents living with HIV. Methods: Semi‐structured individual interviews (IDIs) were conducted from October 2019 to March 2020 with 18 stakeholders with expertise in the (1) development of policy through membership in the Law Society of Kenya or work as a health policy official; (2) review of policy through ethics review committee service; or (3) implementation of policy through involvement in adolescent education. IDIs were conducted in English by Kenyan social scientists, audio‐recorded and transcribed verbatim. We used thematic analysis to identify themes around how policies can be reformed to improve adolescent engagement in HIV care and research. Results: Our analysis identified three major themes. First, policies should be flexible rather than setting an age of consent. Stakeholders noted that adolescents' capacity for engagement in HIV care and research depended on context, perceived risks and benefits, and "maturity"—and that age was a poor proxy for the ability to understand. Second, policies should evolve with changing societal views about adolescent autonomy. Participants recognized a generational shift in how adolescents learn and mature, suggesting the need for a more frequent review of HIV care and research guidelines. Third, adults should empower adolescent decision‐making. Stakeholders felt that caregivers can gradually involve adolescents in decision‐making to equip them to gain ownership over their health and lives, improving their confidence and capacity. Conclusions: Revising relevant laws to consider context, alternative measures of maturity, and evolving societal views about adolescence, along with supporting caregivers to assist in developing adolescent autonomy may promote more equitable and representative participation of adolescents in HIV care and research. Additional research should explore how to support caregivers and other adults to empower adolescents and improve stakeholder engagement in a more routine process of policy reform.